Vom Verstehen zur Verständigung Dokumentation der öffentlichen Vorlesungsreihe zum Europäischen Jahr des Interkulturellen Dialogs 2008 - Casper-Hehne, Hiltraud; Schweiger, Irmy (Universitätsverlag Göttingen, 2009)
This volumes deals with the presentations and debates from the guest lecture series on the occasion of the "European Year of Intercultural Dialogue" 2008 at the Göttingen University.